Belonging in Motion: Contested Social Boundaries in South Asia by Joanna Pfaff-Czarnecka - Pokharel, Binod (Dhaulagiri Journal of Sociology and Anthropology, 2024)
This book is an accumulation of comprehensive work Joanna has done around the area of belonging.